2003
DOI: 10.1021/es034769y
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Musk Fragrances in Lake Michigan

Abstract: Synthetic musk fragrances are added to a wide variety of personal care and household products and are present in treated wastewater effluent. Here we report for the first time ambient air and water measurements of six polycyclic musks (AHTN, HHCB, ATII, ADBI, AHMI, and DPMI) and two nitro musks (musk xylene and musk ketone) in North America. The compounds were measured in the air and water of Lake Michigan and in the air of urban Milwaukee, WI. All of the compounds except DPMI were detected. HHCB and AHTN were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
110
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(124 citation statements)
references
References 38 publications
10
110
0
2
Order By: Relevance
“…29, 2010 1881 ($4) was obtained in human fat samples collected from Austria by Kannan [12]. Peck and Hornbuckle [34] reported that the concentration ratio of HHCB to AHTN in Lake Michigan (USA) waters was 4.7. In China, it has been reported that the ratio of HHCB to AHTN concentrations was 5.3 in sewage sludge collected from the wastewater treatment plants in Guangdong province, and 1.46 in sediment samples from the Pearl River Delta [25].…”
Section: Geographical Trendsmentioning
confidence: 99%
“…29, 2010 1881 ($4) was obtained in human fat samples collected from Austria by Kannan [12]. Peck and Hornbuckle [34] reported that the concentration ratio of HHCB to AHTN in Lake Michigan (USA) waters was 4.7. In China, it has been reported that the ratio of HHCB to AHTN concentrations was 5.3 in sewage sludge collected from the wastewater treatment plants in Guangdong province, and 1.46 in sediment samples from the Pearl River Delta [25].…”
Section: Geographical Trendsmentioning
confidence: 99%
“…Since then, SM have been detected in most environmental matrices, including air (Xie et al 2007), marine water (Xie et al 2007), lake water (Peck and Hornbuckle 2004), sediment (Peck et al 2006), Electronic supplementary material The online version of this article (doi:10.1007/s00477-012-0581-1) contains supplementary material, which is available to authorized users. and sewage sludge (Shek et al 2008;Hu et al 2011b) due to their extensive use.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Two polycyclic musks, galaxolide (1,3,4,6,7,8-hexahydroSynthetic musks (SMs) are ingredients commonly used in 4,6,6,7,8,8-hexamethylcyclopenta-(g)-2-benzopyran, HHCB) personal-care products (PCPs); such musks are generated from and tonalide (7-acetyl-1,1,3,4,4,6-hexamethyl-1,2,3,4 usage by individuals of soaps, shampoo, toothpaste, cosmetics tetrahydronaphthalene, AHTN) as well as two nitro musks, and other daily products. Together with various pharmaceuticals musk xylene (1-tert-butyl-3,5-dimethyl-2,4,6-trinitrobenzene, and other commodities, they constitute a class of pharmaceuticals MX) and musk ketone (1-tert-butyl-3,5-dimethyl-2,6-dinitro-4 and personal-care products (PPCPs) that have been regarded as acetylbenzene, MK) are the most used SMs.…”
Section: Introductionmentioning
confidence: 99%
“…As to the developed countries, introduced into aquatic environments mainly via washing, there is also a need to monitor changes of SMs profiles after the bathing, irrigation and other activities. 4,5 nitro musks have been restricted. In this sense, reliable analytical Because of their highly lipophilic nature, SMs can be methods to simultaneously extract and determine polycyclic bioaccumulated in biota, such as mussels, 6 crustaceans, 7 fish 8-10 musks and nitro musks are critically needed to investigate the and even some mammals 11,12 from the freshwater and marine occurrence, concentration and fate of these chemicals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation